Age-Related Differences in Working Memory Performance in A 2-Back Task - Wild-Wall, Nele; Falkenstein, Michael; Gajewski, Patrick D. (Frontiers in Psychology, 2011)
The present study aimed to elucidate the neuro-cognitive processes underlying age-related differences in working memory. Young and middle-aged participants performed a two-choice task with low and a 2-back task with high working memory load. The P300, an event-related potential reflecting controlled stimulus-response processing in working memory, and the underlying neuronal sources of expected age-related differences were analyzed using sLORETA. Response speed was generally slower for the middle-aged than the young group. Under low working memory load the middle-aged participants traded speed for accuracy. The middle-aged were less efficient in the 2-back task as they responded slower while the error rates did not differ for groups. An age-related decline of the P300 amplitude and characteristic topographical differences were especially evident in the 2-back task. A more detailed analysis of the P300 in non-target trials revealed that amplitudes in the young but not middle-aged group differentiate between correctly detected vs. missed targets in the following trial. For these trials, source analysis revealed higher activation for the young vs. middle-aged group in brain areas which support working memory processes. The relationship between P300 and overt performance was validated by significant correlations. To sum up, under high working memory load the young group showed an increased neuronal activity before a successful detected target, while the middle-aged group showed the same neuronal pattern regardless of whether a subsequent target will be detected or missed. This stable memory trace before detected targets was reflected by a specific activation enhancement in brain areas which orchestrate maintenance, update, storage and retrieval of information in working memory.